The multi-functionality of N-809, a novel fusion protein encompassing anti-PD-L1 and the IL-15 superagonist fusion complex. (1st February 2019) - Jochems, Caroline; Tritsch, Sarah R.; Knudson, Karin M.; Gameiro, Sofia R.; Rumfield, Claire Smalley; Pellom, Samuel T.; Morillon, Y. Maurice; Newman, Robby; Marcus, Warren; Szeto, Christopher; Rabizadeh, Shahrooz; Wong, Hing C.; et al.
ABSTRACT: Here we describe a novel bifunctional fusion protein, designated N-809. This molecule comprises the IL-15/IL15Rα superagonist complex containing the Fc-domain of IgG1 (N-803, formerly designated as ALT-803) fused to two single chain anti-PD-L1 domains. The fully human IgG1 portion of the N-809 molecule was designed to potentially mediate antibody dependent cellular cytotoxicity (ADCC). The studies reported here show that N-809 has the same ability to bind PD-L1 as an anti-PD-L1 monoclonal antibody. RNAseq studies show the ability of N-809 to alter the expression of an array of genes of both CD4 + and CD8 + human T cells, and to enhance their proliferation; CD8 + T cells exposed to N-809 also have enhanced ability to lyse human tumor cells. An array of genes was differentially expressed in human natural killer (NK) cells following N-809 treatment, and there was increased expression of several surface activating receptors; there was, however, no increase in the expression of inhibitory receptors known to be upregulated in exhausted NK cells. N-809 also increased the cytotoxic potential of NK cells, as shown by increased expression of granzyme B and perforin. The lysis of several tumor cell types was increased when either NK cells or tumor cells were exposed to N-809. Similarly, the highest level of ADCC was seen when both NK cells (from donors or cancer patients) and tumor cells were exposed to N-809. These studies thus demonstrate the multi-functionality of this novel agent.